The pharmacology and therapeutic potential of (-)-huperzine A - Tun MK; Herzon SB (Dove Medical Press, 2012)
Maung Kyaw Moe Tun, Seth B HerzonDepartment of Chemistry, Yale University, New Haven, CT, USAAbstract: (–)-Huperzine A (1) is an alkaloid isolated from a Chinese club moss. Due to its potent neuroprotective activities, it has been investigated as a candidate for the treatment of neurodegenerative diseases, including Alzheimer's disease. In this review, we will discuss the pharmacology and therapeutic potential of (–)-huperzine A (1). Synthetic studies of (–)-huperzine A (1) aimed at enabling its development as a pharmaceutical will be described.Keywords: Alzheimer's, NMDA, neurodegeneration, natural products, synthesis